Methicillin-Resistance in Staphylococcus aureus Is Not Affected by the Overexpression in Trans of the mecA Gene Repressor: A Surprising Observation - Oliveira, Duarte C.; de Lencastre, Hermínia (PLOS ONE, 2011)
Methicillin-resistant Staphylococcus aureus (MRSA) is intrinsically cross-resistant to virtually all β-lactam antibiotics. The central determinant for the MRSA phenotype is the mecA gene, whose transcriptional control may be mediated by a repressor (mecI) and a sensor/inducer (mecR1). The mecI-mecR1-mediated induction of mecA takes several hours rendering the strains phenotypically susceptible in spite of the presence of the resistance gene. Therefore, it has been proposed that the full resistance to β-lactams observed in many contemporary clinical MRSA strains requires a non-functional mecI-mecR1 regulatory system. The mecA gene is embedded in a large chromosomal cassette (the SCCmec element) for which several structural types have been described. Some epidemic MRSA clones, typically expressing full β-lactam resistance, carry SCCmec elements that contain an intact mecI-mecR1 locus (e.g. SCCmec types II and III). We have addressed this apparent contradiction by first sequencing the mecI coding region and mecA promoter sequences in a collection of prototype MRSA strains characterized by different SCCmec types. A conserved non-sense mutation within mecI was detected in all SCCmec type III strains tested, presumably responsible for a non-functional truncated MecI protein and, therefore, explaining the full resistance phenotype. In SCCmec type II strains no conserved mutations were found. We next transformed a collection of prototype MRSA epidemic strains with a recombinant plasmid overexpressing a wild-type copy of mecI. Surprisingly, for the great majority of the strains no significant alterations in the phenotypic expression of β-lactam resistance could be detected. These findings were confirmed and further explored, challenging the currently accepted mechanism of mecA transcriptional control. Our observations suggest the existence of yet unidentified additional determinants involved in the transcriptional control of mecA gene and point to a revision of the mecA regulatory mechanism in contemporary MRSA strains.